2010
DOI: 10.15376/biores.6.1.434-446
|View full text |Cite
|
Sign up to set email alerts
|

Discolouration of thermally modified wood during simulated indoor sunlight exposure

Abstract: This paper deals with the effect of UV light through window glass on the changes in colour of surfaces of uncoated and clear-coated thermally modified wood, and on chemical changes of surfaces of uncoated thermally modified and unmodified wood. Discoloration of the uncoated wood samples and those treated with three commercial transparent coatings (two-component polyurethane varnish, water-borne varnish, and nano-impregnation) was measured spectrophotometrically using CIELAB parameters (L*, a*, b* and DE*). FTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…It is easy to see that TM wood exposure to the UV portion of the solar radiation, which caused even greater discoloration of unmodified wood than radiation of full solar spectrum, resulted in much smaller color changes compared with those entailed by the full solar radiation. Reduced discoloration caused by UV irradiation due to wood thermal modification has been observed in a number of researches [37][38][39][40][41]. The phenomena of enhanced resistance to photodiscoloration of TM wood is associated mainly with chemical transformations of lignin, which is well recognized to be the key wood component responsible for its discoloration [37,38,42,43].…”
Section: Tm Wood Color and Its Photosensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to see that TM wood exposure to the UV portion of the solar radiation, which caused even greater discoloration of unmodified wood than radiation of full solar spectrum, resulted in much smaller color changes compared with those entailed by the full solar radiation. Reduced discoloration caused by UV irradiation due to wood thermal modification has been observed in a number of researches [37][38][39][40][41]. The phenomena of enhanced resistance to photodiscoloration of TM wood is associated mainly with chemical transformations of lignin, which is well recognized to be the key wood component responsible for its discoloration [37,38,42,43].…”
Section: Tm Wood Color and Its Photosensitivitymentioning
confidence: 99%
“…It has been found that, similar to unmodified wood, lignin is the most light-sensitive wood component also in TM wood [39,45,46] Therefore, an experiment was carried out by employing an approach that has proved its suitability in case of unmodified wood [23]. The approach includes wood pretreatment prior to coating application with a lignin stabilizer, which is a special HALS designed for trapping the radicals forming at the wood surface.…”
Section: Effect Of Lignin Stabilizermentioning
confidence: 99%
“…У роботі [19] досліджено зміну кольору термомодифікованої деревини як без, та і з додатковим покриттям під час лабораторного впливу ультрафіолетового світла. Виявили кращу стійкість кольору деревини без покриття модифікованої за 190 °C, ніж модифікованої за 212 °C.…”
Section: вступunclassified
“…However, the inherent lighter or darker brown colour is often regarded as another important characteristic of thermally modified (TM) wood that facilitates consumers' preference [6][7][8]. It is also suggested that, due to the colour similarity, TM wood could be used as a substitute for some tropical woods which would be favourable for reducing the over-exploitation of tropical forests [9,10]. Although research results related to outdoor applications dominate in the literature, it is stated that TM wood can be used as well indoors for floorings, decorative panels, kitchen and bathroom furniture, stairs, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although research results related to outdoor applications dominate in the literature, it is stated that TM wood can be used as well indoors for floorings, decorative panels, kitchen and bathroom furniture, stairs, etc. [2,4,9,[11][12][13]. For interior applications, stability of aesthetic appearance is of especial importance and discolouration is a serious problem from the viewpoint of commercial worth of a material [14].…”
Section: Introductionmentioning
confidence: 99%